Routes to Spheroidal Starting Material for Semi-Solid Metal Processing - Asnul Hadi, Ahmad; Naher, S.; S. N., Aqida; D., Brabazon (Elsevier, 2014)
Spheroidal or globular primary phase microstructure is a standard requirement for semi-solid metal (SSM) processing. This type of microstructure improves material formability during processing and allows the production of dense near-net-shape components with detailed geometries. There are many techniques that have been used in order to attain a spheroidal microstructure within the laboratory and industrial settings since the initial discovery of the improved formability provided. The unique forming advantages produced from this type of microstructure are found for both ferrous and non-ferrous materials. Initial laboratory routes for producing semi-solid metal feedstock were based on mechanical stirring methods. In the early 1990’s, semi-solid metal forming was taken on to a greater extent by industry where the main method of feedstock production was electromagnetic stirring. Relatively few large scale aluminium suppliers provided this feedstock to cast houses which in turn formed this into final component geometries. This feedstock was therefore of higher cost than standard aluminium billets and therefore presented a cost barrier to use of the SSM processing route.From the mid-1990’s on, new thermal methods to produce the spheroidal microstructure were developed within which the melt is rapidly solidified and held for a short time in the semisolid state before forming. These techniques allowed for a multitude of small nuclei to be quickly formed and held at a semi-solid temperature during the primary phase spherodised before injection of the material into the mould. Two main advantages of this technique included firstly that the processes had become a single step process and secondly that the technique could be implemented within the cast houses directly rather than requiring purchase of more expensive feedstock and subsequent re-heating. This provided a significant cost reduction for the process and allowed its more widespread use within engineering products. Many research groups have also developed combinations for techniques for production of semi-solid metal feedstock. Though these provide their own individual benefits 4 and drawbacks, these techniques are largely laboratory based due to their higher associated costs. This chapter provides an overview of the techniques that have been used for semi-solid metal feedstock production and provides discussion on the important parameters that need to be well controlled in order to provide the required spheroidal microstructures.